Efficacy of a program to reduce sexual risk behaviors in men who have sex with men - Elías-Risco, Alfonso (2022)
Background: Sexually transmitted diseases (STDs) are a public health problem and the programs to reduce their transmission are mostly addressed from the risk approach and not from a comprehensive intervention. Objective: To evaluate the efficacy of a biographical-professional intervention program with cognitive behavioral techniques to reduce sexual risk behaviors in men who have sex with men (MSM). Method: A two-group pretest-posttest quasi-experimental design was used in the research. The first group consisted of MSM with an STD, nine of whom were in the experimental group and eight in the control group, whereas the second group consisted of MSM with no STD distributed into two groups of 11 men each. The participants answered the questions of an ad hoc scale, whose validity and reliability were previously evaluated. Results: Differences between the experimental and control groups’ pretests and posttests were found, with the experimental group showing a large effect size. Conclusions: The program reduces sexual risk behaviors in MSM; however, in those who suffer from any STD, such behaviors decreased but did not disappear. Authorship contribution AER: design and conception of the study, application of the program, drafting of the article, approval of the final version of the article. GCV: contribution to the design and methodological application of the study, contribution to data processing, critical revision of the manuscript and editing of the article.